Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus - Ivshin, Nikolay; Krutov, Vadim; Romanov, Denis (Zootaxa, 2018)
Two new species and one subspecies of the genus Cechetra Zolotuhin & Ryabov, 2012 are described from South-East Asia. Cechetra bryki sp.n. is described from Nepal, Myanmar (Burma), southwestern China and northern Vietnam. This species is most closely related in habitus, male genitalia morphology and COI mtDNA to the sympatric species, C. lineosa (Walker, 1856) and C. scotti (Rothschild, 1920) in habitus, male genitalia morphology and COI mtDNA. Cechetra inconspicua sp.n. is described from Peninsular Malaysia, Borneo and Sumatra. In habitus, it is closest to C. lineosa and C.subangustata (Rothschild, 1920), but its COI mtDNA (COI-5P “barcode region”) is very different from all other species in the genus. Cechetra subangustata continentalis ssp.n. is described from continental Indochina and Taiwan. It differs from the nominotypical subspecies in habitus. Cechetra scotti comb. nov. is transferred to Cechetra from Cechenena Rothschild & Jordan, 1903.